Socioeconomic and Fiscal Impact of Large-Scale Gold Mining in Mali - Sanoh, Aly (Washington, DC, 2015)
This paper analyzes the socioeconomic, fiscal, and governance impact of gold mining in Mali. The analysis finds that, at the national level, mining plays an important role by contributing to export earnings and overall government fiscal revenue. In 2013, the mining sector represented 7 percent of gross domestic product, contributed 1.5 percent to growth in total gross domestic product, and accounted for 65 percent of total export earnings and 25 percent of total government budget revenues. At the local level, despite higher population growth, there is some evidence that outcomes (poverty and infrastructure services) are marginally better in mining communes compared with non-mining communes. Local governments receive fiscal windfalls that are spent significantly on education capital expenditures and current expenditures (salaries and non-salaries). Non-salary current expenditures are 10 times higher in mining areas. Analysis of the political economy of public service provision at the local level suggests that technical or absorptive capacities may be the bottleneck to increasing the local benefit of mining instead of corruption or accountability.